Hearing the signal of dark sectors with gravitational wave detectors - Jaeckel, Joerg; Khoze, Valentin V.; Spannowsky, Michael (Physical review, 2016)
Motivated by advanced LIGO (aLIGO)’s recent discovery of gravitational waves, we discuss signatures of new physics that could be seen at ground- and space-based interferometers. We show that a first-order phase transition in a dark sector would lead to a detectable gravitational wave signal at future experiments, if the phase transition has occurred at temperatures few orders of magnitude higher than the electroweak scale. The source of gravitational waves in this case is associated with the dynamics of expanding and colliding bubbles in the early universe. At the same time we point out that topological defects, such as dark sector domain walls, may generate a detectable signal already at aLIGO. Both bubble and domain-wall scenarios are sourced by semiclassical configurations of a dark new physics sector. In the first case, the gravitational wave signal originates from bubble wall collisions and subsequent turbulence in hot plasma in the early universe, while the second case corresponds to domain walls passing through the interferometer at present and is not related to gravitational waves. We find that aLIGO at its current sensitivity can detect smoking-gun signatures from domain-wall interactions, while future proposed experiments including the fifth phase of aLIGO at design sensitivity can probe dark sector phase transitions.